The Effect of Service Quality and Facilities on Patient Satisfaction at the Pasar Manna Community Health Centre in South Bengkulu Regency - Fadila Putri Lauara; Ida Anggriani; Kamelia Astuty; Nia Indriasari (Universitas Dehasen Bengkulu, 2026)
Health centers, as primary health facilities, play a strategic role in providing health services to the community. However, based on conditions in the field, there are still several problems, such as long waiting times for services and limited supporting facilities. These conditions can cause a gap between patients' expectations and the services they receive, so research is needed to determine the extent to which service quality and facilities affect patient satisfaction. The research population was patients at Pasar Manna Health Center, with a sample size of 97 respondents determined using the Slovin formula and accidental sampling technique. Data collection was conducted through a questionnaire with a Likert scale that had been tested for validity and reliability. The data obtained were analyzed using multiple linear regression with the help of the SPSS program, and the coefficient of determination and hypothesis testing were conducted partially and simultaneously. The results showed that service quality and facilities had a positive and significant effect on patient satisfaction, both partially and simultaneously. Service quality had a more dominant influence than facilities. Based on these results, it can be concluded that improving service quality and providing adequate facilities are very important in increasing patient satisfaction. Therefore, Pasar Manna Health Center is advised to continue improving service quality and completing facilities to meet the expectations and needs of the community.